Early deformation structures connected to the progradation of a carbonate platform: The case of the Nuvolau Cassian platform (Dolomites - Italy). (April 2022) - Menegoni, Niccolò; Inama, Riccardo; Crozi, Matteo; Perotti, Cesare
Abstract: Among the several Triassic carbonate platforms of the Dolomites, the high and vertical cliff of the Gusela del Nuvolau Cassian carbonate platform provides one of the best exposures of a platform - basin transition. However, its analysis using traditional filed surveys can often be limited and distorted due to the difficult and often impossible accessibility of its walls and the lack of optimal observation points. For this reason, in this study an analysis based on the Digital Outcrop Model (DOM) developed by Uncrafted Aerial Vehicle (UAV) digital photogrammetry technique was used. The 3D DOM analysis allowed to properly determine the stratal geometry and the fracture network of the carbonate platform and underlying basinal deposits (San Cassiano Formation) and to identify the presence of early deformation structures. These structures were probably driven by the differential compaction of the basinal facies that is due the differential load of the carbonate platform as confirmed by the numerical 2D models. These structures are generally orthogonal to the NE progradation direction of the carbonate platform, as in the nearby Lastoni di Formin platform. Highlights: the UAV photogrammetry allows to overcome the limitations of traditional surveys and terrestrial remote sensing techniques. 3D DOM analysis and 2D numerical models suggest the presence of differential compaction driven early deformation structures. 3 fracture sets trending NW, NNW and NE affect the Nuvolau platform. Some NW structures are normal synsedimentary faults. the NE progradation of the platform is approximately orthogonal to the early deformation faults and fractures.